Pengaruh Lingkungan Kerja Fisik dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Dyna Tangerang Selatan - Fahmi Susanti; Laila Lstiani Putri; Indri Indirasari (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Employee performance is a critical factor in achieving organizational goals, and it can be significantly influenced by the work environment and work discipline. In the context of PT Dyna – South Tangerang, understanding these factors is essential to enhance productivity and employee satisfaction. This study aims to examine the effect of the work environment and work discipline on employee performance, both individually and simultaneously. A quantitative research method was employed, using random sampling, resulting in a sample of 51 respondents. Data were analyzed using SPSS version 26, and the analysis techniques included simple and multiple linear regression, correlation coefficient, coefficient of determination, validity and reliability tests, normality, heteroscedasticity, multicollinearity, autocorrelation tests, as well as t-tests and F-tests. The results indicate that both the physical work environment and work discipline have a significant positive effect on employee performance. Employees who work in a comfortable, safe, and supportive environment and exhibit high levels of discipline tend to perform better. Moreover, the combined influence of a conducive work environment and strong discipline creates a positive synergy that enhances motivation, efficiency, and overall work quality. These findings highlight the importance for organizations to invest in improving workplace conditions and fostering a disciplined work culture as strategic approaches to boost performance and productivity.